2023
DOI: 10.3390/healthcare11040611
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Care for Non-COVID-19 Patients with Severe Chronic Illnesses during COVID-19 Pandemic: A Qualitative Study of Healthcare Providers Working around Acute Care Hospitals in South Korea

Abstract: Background: The COVID-19 epidemic has afflicted patients with severe chronic illnesses who need continuous care between home and hospitals. This qualitative study examines the experiences and challenges of healthcare providers around acute care hospitals who have cared for patients with severe chronic illness in non-COVID-19 situations during the pandemic. Methods: Eight healthcare providers, who work in various healthcare settings around acute care hospitals and frequently care for non-COVID-19 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In addition, the COVID-19 pandemic put a great deal of pressure on the capacities of health systems, particularly during the early stages. The inadequacy or sometimes the lack of buildings, health-care workers, and medical care equipment in hospitals increased the workload of health workers (Winkelmann et al, 2022;Adatara et al, 2023;Karakose et al, 2021;Kim et al, 2023). With all these outcomes, the COVID-19 pandemic has become one of the most difficult crises faced by humanity in modern history (Karakose, 2021).…”
Section: Covid-19 Pandemic and Its Impact On Educationmentioning
confidence: 99%
“…In addition, the COVID-19 pandemic put a great deal of pressure on the capacities of health systems, particularly during the early stages. The inadequacy or sometimes the lack of buildings, health-care workers, and medical care equipment in hospitals increased the workload of health workers (Winkelmann et al, 2022;Adatara et al, 2023;Karakose et al, 2021;Kim et al, 2023). With all these outcomes, the COVID-19 pandemic has become one of the most difficult crises faced by humanity in modern history (Karakose, 2021).…”
Section: Covid-19 Pandemic and Its Impact On Educationmentioning
confidence: 99%
“…Furthermore, the pandemic has led to a shortage of healthcare workers due to illness or quarantine measures. This further strained an already overburdened healthcare system, reducing access to essential neonatal care services (20).…”
Section: The Impact Of Covid-19 Neonatal Services In Developing Count...mentioning
confidence: 99%
“…The COVID-19 pandemic has significantly affected hospital admissions for non-COVID-19 patients around the world. While only urgent procedures were performed, all elective and routine diagnostic procedures, as well as routine follow-ups, were postponed and regulated by newly issued protocols [7,[14][15][16][17][18]. O'Conell et al reported a 42,8% reduction in patients admitted for general surgery between 1 March and 30 April 2020 [19,20].…”
Section: Introductionmentioning
confidence: 99%